Aeroelastic flutter analysis of supersonic wing with multiple external stores - Abdullah, Nur Azam; Sulaeman, Erwin (IIUM Press, 2014)
Flutter may be considered to be one of the most dangerous aeroelastic failure phenomenon. The flutter characteristic differs for each aircraft type, and depends on the wing geometry as well as its operational region of subsonic, transonic or supersonic speeds. Prior to performing a flight flutter test, extensive numerical simulations and Ground Vibration Tests should be conducted where the structural finite element modes and the experimentation results should be matched, otherwise the numerical simulation model must be rejected. In this paper, the analysis of simulation of a supersonic wing equipped with external missiles loaded on the wing is presented. The structural mode shapes at each generated frequency are also presented. The analysis is carried out using MSC Nastran FEM software. The wing flutter with the external stores was simulated at different altitudes. The result shows that the flutter velocity is sensitive to the flight altitude. For this reason, the flutter analysis is conducted also for a negative altitude. The negative altitude is obtained by considering the constant equivalent speed- Mach number rule at the flutter speed boundary which is a requirement in standard transport aircraft regulations